Effects of tai chi based on information and communication technology for patients with mild cognitive impairment on cognitive and physical function: a systematic review and meta-analysis - Li, Yezi; Wang, Qingjie; Ren, Yuanyuan; Mao, Xiaokun (Frontiers in Public Health, 2025)
ObjectiveThis study evaluated the effectiveness of tai chi, enhanced by communication technologies, in improving cognitive and physical functioning in patients with mild cognitive impairment, and to compare these effects with traditional tai chi.MethodsA systematic search across four academic databases identified 16 studies with 1,877 participants. Data were expressed as weighted or standardized mean differences with 95% confidence intervals.ResultsA meta-analysis revealed significant improvements in Mini-Mental State Examination scores and Timed Up and Go results in patients with mild cognitive impairment following tai chi intervention. Subgroup analysis indicated that both communication technology-based tai chi and traditional tai chi produced varying improvements in cognitive and physical function.ConclusionThis study confirms the importance of tai chi for cognitive and physical functioning in patients with mild cognitive impairment. Compared with traditional tai chi, communication technology-based tai chi showed greater benefits in promoting rehabilitation. The effective and feasible interventions could improve the physical health of many older adult patients, these findings provide valuable insights and decision-making guidance for clinical practice and public health with older patients with mild cognitive impairment.Systematic review registrationPROSPERO, CRD42023449711, available from: https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023449711.